2019
DOI: 10.30858/zer/115186
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Awareness of Farmers and Farms’ Characteristics

Abstract: The major objective of the article was to assess how farmers perceive the environmental impact of agriculture and to identify the characteristics of farms managed by farmers differing in terms of environmental awareness. The studies covered 600 commercial farms across Poland, participating in the FADN. Awareness of farmers in this area was assessed using the Likert scale. Depending on the included element of the natural environment, from about 30 to 60% of the farmers were aware of the negative environmental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…In the area of benefits for society, the production of safer food was identified as the most important, which is related to its impact on health. Sulewski and Gołaś (2019) came to similar conclusions in their research, who stated that farmers indicated the care for health as the main motive justifying the need to protect the environment. Further aspects include improving working conditions on a farm, improving livestock welfare and increasing the attractiveness of rural areas.…”
Section: Resultssupporting
confidence: 55%
“…In the area of benefits for society, the production of safer food was identified as the most important, which is related to its impact on health. Sulewski and Gołaś (2019) came to similar conclusions in their research, who stated that farmers indicated the care for health as the main motive justifying the need to protect the environment. Further aspects include improving working conditions on a farm, improving livestock welfare and increasing the attractiveness of rural areas.…”
Section: Resultssupporting
confidence: 55%
“…It is necessary not so much to accelerate changes in farmers' awareness but to implement appropriate practices in the scope of nature conservation and use of biological resources in a sustainable manner (precision farming, etc.). A relatively high level of awareness among Polish farmers in the scope of the natural environment is also presented in other publications (Kaczocha and Sikora 2016;Sulewski and Gołaś 2019).…”
Section: Results Of the Research And Discussionmentioning
confidence: 68%
“…In this respect, it is noticed that the impact of agriculture on soil degradation processes is due to, inter alia, improper practices such as crop rotation and fertilization, agrotechnical treatments, depletion, etc. (Sulewski & Gołaś, 2019). From the very beginning, it was clear that the reuse of wastewater is a good opportunity to increase the efficiency in agriculture but it cannot be done directly without any control or regulation.…”
Section: Abstraktmentioning
confidence: 99%